Pengaruh Motivasi dan Etos Kerja Terhadap Kinerja Guru SMA Negeri Program Sekolah Penggerak - Febri Satriani; Syaiful Eddy; Nur Ahyani (Journal Of Administration and Educational Management (ALIGNMENT), 2023)
The purpose of this study was to analyze and describe the influence of motivation and work ethic together on the performance of teachers of State Senior High Schools in the Mobilization Program throughout the Kayuagung District. This research is a quantitative research with a causal study form. The population in this study were all school principals and teachers who served in State Senior High Schools in the Kayuagung District, totaling 137 people. The number of samples was calculated using the Slovin formula with a result of 58 people. The method of collecting data in this study is a questionnaire/questionnaire method, documentation and observation. Data analysis techniques in this study used descriptive analysis of data, independent variable descriptive analysis, dependent variable descriptive analysis and statistical analysis of research data. The results of this study are that there is an influence between motivation and work ethic together on the performance of teachers of Public High School Program Mobilization Schools throughout the Kayuagung District with an influence contribution of 29.6%. The fundamental difference from this research is that the research subjects specifically examined driving schools in the Kayuagung sub-district. In conclusion, there is a simultaneous influence of motivation and work ethic on the performance of teachers of Public High Schools in the Mobilization School Program throughout the Kayuagung District Keywords: Drive School, Motivation, Teacher Performance, Work Ethic